Very Long-Chain Acyl-CoA Dehydrogenase Deficiency: High Incidence of Detected Patients With Expanded Newborn Screening Program - Remec, Ziga I.; Groselj, Urh; Drole Torkar, Ana; Zerjav Tansek, Mojca; Cuk, Vanja; Perko, Dasa; Ulaga, Blanka; Lipovec, Neza; Debeljak, Marusa; Kovac, Jernej; Battelino, Tadej; Repic Lampret, Barbka (Frontiers in Genetics, 2021)
Very long-chain acyl-CoA dehydrogenase deficiency (VLCADD) is a rare autosomal recessive disorder of fatty acid metabolism with a variable presentation. The aim of this study was to describe five patients with VLCADD diagnosed through the pilot study and expanded newborn screening (NBS) program that started in 2018 in Slovenia. Four patients were diagnosed through the expanded NBS program with tandem mass spectrometry; one patient was previously diagnosed in a pilot study preceding the NBS implementation. Confirmatory testing consisted of acylcarnitines analysis in dried blood spots, organic acids profiling in urine, genetic analysis of ACADVL gene and enzyme activity determination in lymphocytes or fibroblasts. Four newborns with specific elevation of acylcarnitines diagnostic for VLCADD and disease specific acylcarnitines ratios (C14:1, C14, C14:2, C14:1/C2, C14:1/C16) were confirmed with genetic testing: all were compound heterozygotes, two of them had one previously unreported ACDVL gene variant each (NM_000018.3) c.1538C>G; (NP_000009) p.(Ala513Gly) and c.661A>G; p.(Ser221Gly), respectively. In addition, patient diagnosed in the pilot study also had specific elevation of acylcarnitines. Subsequent ACDVL genetic analysis confirmed compound heterozygosity. In agreement with the diagnosis enzyme activity was reduced in four patients tested. In seven other newborns with positive screening results, only single allele variants were was found in ACDVL gene, so the diagnosis was not confirmed. Among these, two variants were novel, c.416T>C and c.1046C>A respectively (p.Leu139Pro and p.Ala349Glu). In the first two years of the expanded NBS program in Slovenia altogether 30,000 newborns were screened. We diagnosed four cases of VLCADD. The estimated VLCADD incidence was 1:7,500 which was much higher than that of the medium-chain acyl-CoA dehydrogenase deficiency (MCADD) cases in the same period. Our study also provided one of the first descriptions of ACADVL variants in Central-Southeastern Europe and reported of 4 novel variants.